Compositional design and optimization of dentin adhesive with neutralization capability. Issue 9 (September 2015) - Song, Linyong; Ye, Qiang; Ge, Xueping; Spencer, Paulette
Abstract Objectives The objective of this work was to investigate the polymerization behavior, neutralization capability, and mechanical properties of dentin adhesive formulations with the addition of the tertiary amine co-monomer, 2-N-morpholinoethyl methacrylate (MEMA). Methods A co-monomer mixture based on HEMA/BisGMA (45/55, w/w) was used as a control adhesive. Compared with the control formulation, the MEMA-containing adhesive formulations were characterized comprehensively with regard to water miscibility of liquid resin, water sorption and solubility of cured polymer, real-time photopolymerization kinetics, dynamic mechanical analysis (DMA), and modulated differential scanning calorimetry (MDSC). The neutralization capacity was characterized by monitoring the pH shift of 1 mM lactic acid (LA) solution, in which the adhesive polymers were soaked. Results With increasing MEMA concentrations, experimental copolymers showed higher water sorption, lower glass transition temperature and lower crosslinking density compared to the control. The pH values of LA solution gradually increased from 3.5 to about 6.0–6.5 after 90 days. With the increase in crosslinking density of the copolymers, the neutralization rate was depressed. The optimal MEMA concentration was between 20 and 40 wt%. Conclusions As compared to the control, the results indicated that the MEMA-functionalized copolymer showed neutralization capability. The crosslinking density of the copolymer networks influenced the neutralization rate.